Pemanfaatan Digital Forensik dalam Usaha Preventif Penumpasan Penyebaran Berita Bohong (Hoax) (Postulat, 2023)
In 2018, there were at least 10 fake news stories circulating involving various topics and subjects, ranging from natural disasters, abuse cases, child kidnappings, and the spread of toxic materials. The high number of fake news stories in the era of globalization and the spread of breaking news cannot be separated from the way people consume online media and advances in information technology itself. To overcome this problem, several countries have formed special police units whose job it is to investigate crimes in cyberspace. One of the steps that can be taken to facilitate the investigation of data privacy cases is digital forensics, which is a procedure for investigating computer crimes in the cyberworld. In this journal, the author chooses to apply associative research (relationships) with legal material tracing techniques using library research techniques, as well as analysis of studies using qualitative analysis related to the use of digital forensics in efforts to prevent the spread of fake news (hoaxes). Based on the results of the discussion, it can be concluded that, in a preventive effort to suppress the spread of hoaxes, the use of digital forensics is very influential in suppressing the spread of hoaxes, especially in the specializations of computer forensics, mobile forensics, and cyber forensics. The results of the analysis, review, and examination of evidence from the three specializations are strong and fundamental evidence in efforts to prevent the spread of fake news (hoaxes).